Partisipasi Masyarakat dalam Pengelolaan Kebersihan Pantai Gajah di Kelurahan Air Tawar Barat Kecamatan Padang Utara Kota Padang - Sya’bani, Nur; Wilis, Ratna (Lembaga Yasin AlSys, 2023)
This research aims to find out how the community participates in the cleanliness of Gajah Beach, North Padang District, Padang City. The Elephant Beach tourist attraction in Padang City is one of the famous tourist assets in the city of Padang which is visited by many local people and outside the city and must be kept clean. However, what is currently happening is that there are many piles of rubbish scattered and strewn along the beach, thus disrupting the comfort of beach visitors and also disrupting the health of the people around the beach. The research results show that community participation in managing cleanliness at Gajah Beach is divided into three forms, namely financial (money & goods), energy and thoughts/ideas. However, among the three forms of participation, participation in the form of goods and labor is the most dominant given by the community because it is in line with its implementation. This shows that there are still many people who are unable to contribute in the form of money due to income factors, but can participate in the form of labor later in life. form of goods. The factors that influence community participation are awareness factors, age factors, education factors, income/income factors, and lack of public understanding.